Profit sharing and unemployment: An approach with bargaining and efficiency wage effects - Erkki Koskela; Rune Stenbacka (The Research Institute of the Finnish Economy (ETLA), 2003)
We offer a unified framework to analyze the determination of employment, employee effort, wages and profit sharing when firms face stochastic revenue shocks. We apply a generalized Nash bargaining solution, which extends the wage bargaining literature by incorporating efficiency wage considerations, profit sharing and exogenous capital structure. The profit sharing instrument is demonstrated to have positive effort-enhancing and wage-moderating effects, which exactly offset the negative dilution effect in equilibrium. We show that introduction of profit sharing decreases equilibrium unemployment if the benefit replacement ratio is high enough, whereas the reverse holds if the benefit replacement ratio is below this threshold.
Keywords: J51; J41; G32; 330; Tarifliche Gewinnbeteiligung; Arbeitslosigkeit; Effizienzlohn; Schwedisch-Finnland